2013
DOI: 10.4236/acs.2013.33041
|View full text |Cite
|
Sign up to set email alerts
|

Aquacrop Model Calibration in Potato and Its Use to Estimate Yield Variability under Field Conditions

Abstract: AquaCrop model estimates the crop productivity decrease in response to water stress, determining the biomass (B) based on water productivity (WP) and accumulated transpiration (ΣTr); and the yield (Y) is calculated according to B and the harvest index (HI). AquaCrop was evaluated considering different WP values for 2010 late growing season to simulate crop yield of potato (Solanum tuberosum L.) cv. Spunta, in a commercial production field of 9 ha located in the green belt of Cordoba city (31˚30'S, 64˚08'W, 402… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
4
12
0
1
Order By: Relevance
“…For all fields, the values of CC were generally overestimated from the senescence to the end of the cropping season as also highlighted by Andarzian et al (2011) for wheat production under full and deficit water conditions in Iran. Overall, the obtained results in estimating CC are satisfactory and are in agreement with other studies using the same model with different crops, such as barley (Araya et al, 2010) and corn, tomato and potato crops (Casa et al, 2013;Katerji et al, 2013). Fig.…”
Section: Validation Of the Aquacrop Modelsupporting
confidence: 90%
“…For all fields, the values of CC were generally overestimated from the senescence to the end of the cropping season as also highlighted by Andarzian et al (2011) for wheat production under full and deficit water conditions in Iran. Overall, the obtained results in estimating CC are satisfactory and are in agreement with other studies using the same model with different crops, such as barley (Araya et al, 2010) and corn, tomato and potato crops (Casa et al, 2013;Katerji et al, 2013). Fig.…”
Section: Validation Of the Aquacrop Modelsupporting
confidence: 90%
“…Furthermore, the deviation between observed and simulated daily CC and biomass was more pronounced under water deficit conditions, becoming more intense as stress levels increased. The larger deviation between observed and simulated CC under water deficit and stress environments has also been reported for other crops like potatoes [15]. The general tendency of AquaCrop simulation model to overestimate maize biomass under water deficit conditions has been reported by Heng et al [8], who contribute the deviation to vegetative stress and suggest that this can be attributed to the actual stomatal conductance being less than that simulated.…”
Section: Discussionmentioning
confidence: 70%
“…Still, some studies report that model performance declines in estimating some variables in severe water stress environments [1,13]. Although a highlighted feature of the model is the applicability of conservative parameters used in crop simulations (these parameters are reported by Heng et al [8] and Hsiao et al [12] for maize), several researchers observed that model parameterization is essentially site-specific and that important calibrated parameters necessary for accurate simulation must be tested under different climate, soil, cultivars, irrigation methods, and field management to improve the reliability of the simulated results [3,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as a valuable tool for improving irrigation water productivity in crop production planning [6,50]. AquaCrop has been calibrated and parameterised to various crops under various environmental and irrigation conditions, including barley [51], soybean [52], sunflower [53], cotton [54,55], corn [56], sugar beet [57], wheat [58,59], potato [60,61], cabbage [62], and rice [63]. However, this has not yet been done in the case of lettuce.…”
Section: Introductionmentioning
confidence: 99%